2011
DOI: 10.1089/mdr.2011.0098
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Distribution of β-Lactamase A (blaA) and β-Lactamase B (blaB) Genes in Enteropathogenic Yersinia Species

Abstract: One hundred eighty-six strains of enteropathogenic Yersinia (Y.) enterocolitica of bioserotypes 2/O:5,27, 2/O:9, 3/O:3, and 4/O:3 and 12 strains of Yersinia pseudotuberculosis of bioserotypes 1/O:1, 1/O:2, and 2/O:1 from different human (feces) and nonhuman (pig, pork, wild boar, monkey, chinchilla, mara, capybara, salad) sources collected in the years 1995-2009 were examined. Antimicrobial resistance patterns for 12 antimicrobial agents were generated using broth microdilution. The presence and characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
2
25
1
2
Order By: Relevance
“…enterocolitica 4/O:3 isolates from the Abidjan district were susceptible to most antibiotics commonly used to treat Gram-negative enteropathogens, and were resistant to penicillin and first and second-generation cephalosporin, due to the presence of the chromosomal blaA and blaB genes [71,72]. If the diagnosis of yersiniosis is not made, these classes of antibiotics may be used to treat patients, thus leading to treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…enterocolitica 4/O:3 isolates from the Abidjan district were susceptible to most antibiotics commonly used to treat Gram-negative enteropathogens, and were resistant to penicillin and first and second-generation cephalosporin, due to the presence of the chromosomal blaA and blaB genes [71,72]. If the diagnosis of yersiniosis is not made, these classes of antibiotics may be used to treat patients, thus leading to treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Los genes de BlaA y BlaB se encuentran en la mayoría de las cepas, pero la expresión de una u otra depende del serotipo 42,43 . La expresión de ambas daría un perfil de resistencia a aminopenicilinas, carboxipenicilinas, cefalosporinas de primera generación, cefoxitina y amoxicilina-clavulánico.…”
Section: Yersinia Enterocoliticaunclassified
“…La tasa de resistencia a cotrimoxazol es inferior al 2%, y en el caso de las tetraciclinas no supera el 1% 13,[42][43][44]46 .…”
Section: Yersinia Enterocoliticaunclassified
“…Etiology Infection with the gram-negative, rodshaped, facultative anaerobic bacteria Yersinia pseudotuberculosis (Langford, 1972;Hubbert, 1972) and Y. enterocolitica (Bonke et al, 2011;Raevuori et al, 1979;Wuthe and Aleksic, 1992;Hubbert, 1972) have been reported in the chinchilla.…”
Section: Yersinia Sppmentioning
confidence: 99%